2008
DOI: 10.1017/s0265021508004195
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil-TCI and propofol-TCI for conscious sedation during fibreoptic intubation in the acromegalic patient

Abstract: Remifentanil and propofol target-controlled infusion provided satisfactory conscious sedation allowing for successful oral fibreoptic intubation in acromegalic patients with no recall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…9,10,[14][15][16] More recently, case reports have described the concurrent use of propofol TCI with remifentanil TCI for AFOI [14][15][16] Authors describing the combined use of TCI propofol and remifentanil for AFOI have reported mean effect-site concentrations during the procedure of 0.8-2.0 lgÁmL -1 and 1.5-3.2 ngÁmL -1 , respectively. Although there is no evidence supporting the superiority of TCI propofol over a fixed rate infusion in the setting of an AFOI, it is safe to say that a TCI has a more consistent pharmacodynamic effect and may allow for a more predictable level of sedation to be maintained.…”
Section: -13mentioning
confidence: 99%
See 3 more Smart Citations
“…9,10,[14][15][16] More recently, case reports have described the concurrent use of propofol TCI with remifentanil TCI for AFOI [14][15][16] Authors describing the combined use of TCI propofol and remifentanil for AFOI have reported mean effect-site concentrations during the procedure of 0.8-2.0 lgÁmL -1 and 1.5-3.2 ngÁmL -1 , respectively. Although there is no evidence supporting the superiority of TCI propofol over a fixed rate infusion in the setting of an AFOI, it is safe to say that a TCI has a more consistent pharmacodynamic effect and may allow for a more predictable level of sedation to be maintained.…”
Section: -13mentioning
confidence: 99%
“…[20][21][22][23][24] This makes it an attractive drug of choice for the intensely stimulating but usually brief airway manipulation during an AFOI. It is increasingly being used either as the primary agent or in conjunction with midazolam 10,11,25 and, more recently, propofol [14][15][16] to provide sedation during AFOI. Studies evaluating remifentanil as a primary agent have described its use at different set rates of infusion, by bolus dose followed by infusion, and, more recently as a TCI.…”
Section: Remifentanilmentioning
confidence: 99%
See 2 more Smart Citations
“…4,13,20 A cogent plan for intubation based on preoperative airway assessment should be discussed with the anesthesia team. 5,26 Plans for administration of antibiotics, hormone replacement, pretreatment with somatostatin analogs, 8 or any additional perioperative medications should also be addressed in advance. It is imperative that the correct neuroimaging modalities are used and that the studies are carefully and systematically reviewed preoperatively.…”
Section: Operative Strategies For Endoscopic Transsphenoidal Surgery mentioning
confidence: 99%